Exploring Emerging Topics on Antibiotic Use in Brazilian Tweets via Unsupervised Learning - Mazza, Hudson; Berton, Lilian (Anais do Encontro Nacional de Inteligência Artificial e Computacional (ENIAC); 2025: Anais do XXII Encontro Nacional de Inteligência Artificial e ComputacionalDO - 10.5753/eniac.2025.13765, 2025)
Antibiotic misuse plays a critical role in the global spread of antimicrobial resistance, underscoring the need to understand how the public discusses and perceives antibiotic use. This study investigates emerging topics related to antibiotic use among Brazilian Twitter users by applying unsupervised learning techniques. We collected a corpus of Portuguese-language tweets and modeled the textual data using BERTimbau, a language representation model pretrained specifically for Brazilian Portuguese. To uncover latent structures in the data, we applied K-Means clustering on the sentence embeddings, enabling us to identify and interpret thematic groupings within the public discourse. The analysis revealed recurring topics such as respiratory infections, public figures, and self-care dominate discussions. These insights demonstrate the value of combining social media data with unsupervised learning to support public health communication and surveillance strategies in Brazil.